2017
DOI: 10.15171/jcs.2017.004
|View full text |Cite
|
Sign up to set email alerts
|

Stress Management among Parents of Neonates Hospitalized in NICU: A Qualitative Study

Abstract: Introduction: Infant hospitalization is stressful event for parent in NICU. Parents think that they have lost control because of unfamiliar environment. Therefore, stress management is very important in this period. The family as the main factor of strength and protection for infant is required as the bases of standard care in NICU. Therefore the aim of this study was to investigate stress management in Iranian NICU Parents. Methods: Using qualitative content analysis approach helped to collect and analysis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 33 publications
(33 reference statements)
3
29
0
4
Order By: Relevance
“…This study showed that more than half of parents experienced high levels of stress, and one in four, the average level. This corresponds to the results of other authors [4,[6][7][8] who confirmed the occurrence of a high level of stress in parents. Thus, the question arises how to take care of a newborn and their parents to minimize the stimuli that cause tension and are a source of stress?…”
Section: Poziom Stresu I Umiejscowienie Kontroli Zdrowia U Rodziców Hsupporting
confidence: 92%
See 3 more Smart Citations
“…This study showed that more than half of parents experienced high levels of stress, and one in four, the average level. This corresponds to the results of other authors [4,[6][7][8] who confirmed the occurrence of a high level of stress in parents. Thus, the question arises how to take care of a newborn and their parents to minimize the stimuli that cause tension and are a source of stress?…”
Section: Poziom Stresu I Umiejscowienie Kontroli Zdrowia U Rodziców Hsupporting
confidence: 92%
“…The impact of strong stressors and the lack of well-shaped personality defence mechanisms can have serious health consequences for humans. Emotional disorders, increased anxiety, sleep and appetite disorders are characteristic features [1][2][3][4][5][6][7][8][9]. In the presented research results, more than half (66.2%) of parents experienced concern, 41.9% fear, and almost every third anxiety.…”
Section: Poziom Stresu I Umiejscowienie Kontroli Zdrowia U Rodziców Hmentioning
confidence: 89%
See 2 more Smart Citations
“…Parents already in shock from an unexpected early birth, frequently find the NICU environment overwhelming, due to seeing their infant connected to wires, electrodes and intravenous lines, and the unfamiliar equipment such as an incubator, cardiac monitor, and ventilator. [10] Hence, most parents are not prepared for the challenges of parenting a preterm infant. [11] Though parents have a vital role in caring for their infant beginning in the NICU, they have specific information and communication needs, and they seek ways to reduce the emotional impact of their infant's admission to the NICU.…”
Section: Introductionmentioning
confidence: 99%